2017
DOI: 10.1186/s40816-017-0042-y
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, antioxidant and anticancer properties of Turbinaria conoides (J. Agardh) Kuetz

Abstract: Background: Cancer causes leading death in the world population due to exposure of various carcinogenic/mutagenic agents, radiation and life style. There are 2.6 million new cases diagnosed each year. Therefore, the objective is aimed to study the antibacterial and antioxidant activities of solvent fractions of ethanolic extract of T. conoides and its anticancer activity also evaluated by analyzing cytotoxicity, cell cycle arrest and apoptosis in HepG2 cell line. Methods: Antibacterial activity was done by dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 28 publications
1
13
0
2
Order By: Relevance
“…Such a process is represented by some of the biological defense mechanisms in plants. These findings agree with those reported by Ponnan et al, (2017) who investigated that seaweeds could be used as fertilizer and pesticide. Nabanita et al, (2010) reported that most of the common phytochemicals are present in T. conoides.…”
supporting
confidence: 93%
“…Such a process is represented by some of the biological defense mechanisms in plants. These findings agree with those reported by Ponnan et al, (2017) who investigated that seaweeds could be used as fertilizer and pesticide. Nabanita et al, (2010) reported that most of the common phytochemicals are present in T. conoides.…”
supporting
confidence: 93%
“…In the present study, with increasing polarity, three organic solvents like hexane < ethyl acetate < methanol along with the water used for the extraction of crude extracts from three different species of marine algae. In the case of Turbinaria conoide highest antibacterial activity was exhibited in ethanol extract, which was comparable to the standard, Streptomycin against Bacillus subtilis, Enterococcus faecalis and Pseudomonas aeruginosa 15 . There was no anti-bacterial, activity shown in Methanol extract of Sargassum vulgare against Escherichia coli and Staphylococcus aureus 16 .…”
Section: Fig 4: Gc-ms Profile Of Compounds In Turbinaria Conoides Crmentioning
confidence: 75%
“…Sodium alginate (Figure 4J) obtained from brown seaweeds has shown antitumor and anti-inflammatory properties [132]. The anticancer activity was evaluated by analyzing the effects on the cell cycle and apoptosis induction on HepG2 cells [133]. Furthermore, several studies validated the apoptosis induction ability of fucoidans in various tumor cell lines, including melanoma cells, colon cancer, lymphoma, and breast cancer cells [134].…”
Section: Metabolites With Potential Beneficial Activities From Marmentioning
confidence: 99%